A Fading Decision - Fewing, Ross (The Hastings Center report, 2014)
Mrs. F, seventy-five, was diagnosed with Alzheimer's. She and her spouse often discussed how to handle the progression of the disease. She was adamant about not coming to the point where she would be unable to recognize herself, her husband, or their son and daughter. The manner she chose was voluntarily stopping eating and drinking (VSED), and she chose a specific date on which to carry out her plan. She asked her husband to promise, should she ever waver and request nutrition or hydration, to remind her of the reasons she had chosen for pursuing this path. Mrs. F's ability to function was beginning to wax and wane. Sometimes she was her old self, and sometimes she had no recollection of her past identity. After she voluntarily stopped eating and drinking, the couple's promise created a dilemma for her professional caregivers. She asked for food and drink. Her husband and family reminded her of the reasons she had chosen VSED: “Remember, you didn't want to live in a nursing home, and you didn't want us to be responsible for caring for you at home. You believe that stopping eating and drinking will allow you to die with dignity.” Although they also asked Mrs. F, “What do you want to do?” the family asked the professional caregivers to respect her original choice to stop eating and drinking. Mrs. F still evidenced decision-making capacity but often did not recall having chosen VSED. She again requested food and drink, from family and the professional caregivers. Can VSED be carried out for a patient whose advanced dementia makes disciplined voluntary action difficult?